Mental health of health-care workers during the COVID-19 pandemic - Mogassabi, Walaa; Mogassabi, Waqar; Saliba, Maram; Emam, Rana; Ibrahim, Wanis (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Besides its effects on physical health, the coronavirus disease 2019 (COVID-19) pandemic has resulted in adverse consequences on mental health of health-care workers. Several factors such as safety concerns and fear of infecting self or family members, social isolation measures, strict infection control procedures, lack of protective measures, exhaustion due to increased duration of working, and seeing patients die or colleagues infected can contribute to the development of mental health problems in health-care workers during the current COVID-19 pandemic. Some health-care staff including nurses, advanced practice providers, frontline health-care workers, and health-care workers who have children are more vulnerable to these mental health problems. Prevention of infection and staff burnout in health-care workers, provision of a timely mental health care, and social support are among the most important measures to provide a mental health care for health-care workers during the current COVID-19 pandemic.
Keywords: COVID-19; health-care workers; mental health; pandemic; SARS-CoV-2